Implementasi Pembelajaran Kitab Kuning Sebagai Upaya Peningkatan Religiusitas Peserta Didik di Pondok Pesantren Terpadu Nurul Islam Blang Rakal Kabupaten Bener Meriah - Jufrizal (Malewa: Journal of Multidisciplinary Educational Research, 2023)
The introduction of religious values ​​and the introduction of students to the yellow book as a bridge to be able to learn the basics of the book, namely the Koran and Hadith. Studying the yellow book also includes studying interpretations of the Koran and hadith. Because it will be dangerous if children are accustomed to taking arguments from the Koran even though they don't know the interpretation. This research uses qualitative research with a field approach. The data collection that researchers used was interviews, observation and documentation. In analyzing data, researchers used data analysis techniques. The findings of this study are: the implementation of learning the yellow book as an increase in the religiosity of students at the Nurul Islam Integrated Islamic Boarding School can increase the religiosity of students along with the books they master. This learning provides an essence on an ongoing basis in increasing the intensity of the frequency of faith and understanding of everything related to Islamic religious teachings, because the study of the yellow book explores Islamic religious teachings in detail in relation to religiosity in the following five dimensions: Aqidah Dimension, Worship Dimension, Dimension Ihsan and Dimensions of Knowledge. Keywords: Implementation, learning the Yellow Book, Religiosity